Test method for measuring current distribution in mixed cathode lithium battery and application
By preparing each material in the hybrid cathode lithium battery into an independent battery cell and measuring its current distribution in parallel, the problem of difficult to measure the current distribution of the hybrid cathode in the prior art is solved, and the charging and discharging performance evaluation of the hybrid system and the effective guarantee of material performance is achieved.
Patent Information
- Application Number
- CN202411549195.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The prior art is difficult to accurately measure the current distribution of each material in a hybrid cathode lithium battery, which affects the charging and discharging performance evaluation of the hybrid system, the rate performance and long cycle performance of the material.
The individual cells are prepared by mixing each material in the lithium battery cathode according to the surface load, and a surface electrode is provided on the negative electrode to form a pure electron loop, the equivalent resistance of each independent cell is measured, and connected in parallel to calculate the current distribution of each material.
Accurate measurement of the current distribution of each material in the hybrid cathode is achieved, reasonable working conditions are designed for the evaluation of the charging and discharging performance of the hybrid system, and the rate performance and long cycle performance of the hybrid system are ensured.
Smart Images

Figure CN119738726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium battery, and in particular to a test method and application for measuring current distribution in a mixed cathode lithium battery. Background Art
[0002] Lithium batteries are widely used in electric vehicles. Power batteries need to have advantages in energy density, cycle life, fast charging, low temperature performance, safety and cost, and develop power batteries with excellent performance in six dimensions. At present, the main positive electrode materials on the market for power batteries are ternary materials and iron-lithium positive electrodes. Among them, ternary materials have the characteristics of high capacity and high working voltage platform, good low temperature performance and good rate performance, and iron-lithium materials have the characteristics of good safety performance and long cycle performance. In order to ensure the low temperature performance, energy density and safety advantages of power batteries, the cathode mixed with iron-lithium positive electrode and ternary materials is also an important development direction for power batteries. When the two materials are mixed, the voltage range of iron-lithium charging is 2-3.8V, and the charging voltage range of ternary materials is 2.5-4.2V. Therefore, the voltage range of mixed materials generally includes the entire voltage range. However, at high voltage, it may be mainly the ternary material that contributes capacity, and the actual rate corresponding to the ternary material may be high. Therefore, the charging current at different voltage ends of the mixed cathode system needs to be considered in many aspects. At present, the capacity performance of hybrid cathode materials during the charge and discharge process is strongly related to the charge and discharge conditions. Therefore, it is necessary to measure the current distribution in the hybrid cathode material so that the charge and discharge conditions of the hybrid cathode can be better formulated.
[0003] In the prior art, someone has developed a method and device for measuring the current distribution of a large-area flat-plate solid oxide fuel cell, including: preparing the battery to be tested into multiple small batteries, testing the power or current density of the multiple small batteries respectively, and determining the current distribution of the battery to be tested based on the current and / or current density of the multiple small batteries obtained by measurement. This solution mainly utilizes a parallel design to divide the current distribution of a large surface into several small surfaces for current measurement, and does not solve the idea of how the cathode of the mixed two materials in the mixed system is equivalent to parallel. In addition, the patent only describes the measurement of the current size of multiple paths separately, but does not specifically describe how to measure.
[0004] In the prior art, a battery system for a secondary battery including a mixed cathode material, and a device and method for managing a secondary battery with a mixed cathode material are disclosed. The scheme mainly explains that the mixed cathode material will relax the voltage within the voltage range of a specific point, and the relaxation current between the two cannot be measured in real time.
[0005] Therefore, it is necessary to develop a test method to accurately measure the current distribution of each material in a hybrid cathode lithium battery, to design more reasonable operating conditions for the charging and discharging performance evaluation of the hybrid system's battery cells, and to ensure the rate performance and long cycle performance of the hybrid system. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology, to provide a test method for accurately measuring the current distribution in a mixed cathode lithium battery, to design more reasonable working conditions for the charging and discharging performance evaluation of the battery cells of the hybrid system, and to ensure the rate performance and long cycle performance of the hybrid system.
[0007] The technical solution of the present invention is: a test method for measuring current distribution in a mixed cathode lithium battery, comprising:
[0008] Prepare independent cells according to the surface loading of each material in the lithium battery mixed cathode, and each independent cell is provided with a surface electrode on the negative electrode to form a pure electronic circuit with the negative electrode tab;
[0009] Determine the equivalent resistance of each independent battery cell;
[0010] After all independent battery cells are connected in parallel, the voltage of each independent battery cell is collected under preset power-on conditions, and the current passing through each independent battery cell is calculated based on the equivalent resistance, which is the current corresponding to each material in the mixed cathode under the preset power-on conditions.
[0011] In the present invention, the hybrid system battery is divided into multiple separate cells through the design of hybrid system equivalence, and then the parallel structure is designed. The surface electrode is used inside a single cell to make the entire cell equivalent to a pure ohmic resistor (a resistor that does not change with the charging SOC and charging current). The real-time reaction current of different materials can be tested based on the surface electrode and the negative electrode voltage side, and more reasonable working conditions can be designed for the hybrid system cell charging and discharging performance evaluation to ensure the rate performance and long cycle performance of the hybrid system.
[0012] Preferably, the surface loading of each material is calculated in the following manner: the overall surface loading of the mixed cathode is A, the mass percentage of each material in the mixed cathode is a, and the surface loading of each material = A·a.
[0013] Preferably, the independent battery cell is a hard-shell battery cell or a soft-pack battery cell, and the surface electrode material of each independent battery cell is consistent with the negative electrode current collector material, and each surface electrode is in the shape of an elongated strip and extends out of the packaging material of the independent battery cell. The independent battery cell is preferably a soft-pack battery cell, which is easier to prepare than a hard-shell battery cell. The surface electrode material and the negative electrode current collector material are consistent, which facilitates the smooth transmission of the loop current. Furthermore, the surface electrode material is a porous copper foil or a copper mesh. In the present invention, a porous copper foil or a copper mesh structure is used on the surface of the graphite negative electrode, and a pure electronic circuit is constructed between the surface electrode and the negative electrode tab, which has the properties of an ohmic resistance. Therefore, under different currents, the voltage between the surface electrode and the negative electrode side satisfies the linear Ohm's law.
[0014] Preferably, the equivalent resistance of each independent battery cell is determined, specifically including: collecting the voltage of each independent battery cell under multiple current conditions, and obtaining the equivalent resistance value according to the corresponding relationship between the collected voltage and current. Further, the voltage of each independent battery cell is collected under multiple current conditions, and a straight line is fitted between the collected voltage and current, and the equivalent resistance value is obtained according to the slope of the straight line. The test of equivalent resistance is performed at a rate of less than 2C as much as possible, generally 5 rate points, which can be selected from the commonly used rate points (such as 0.1C, 0.2C, 0.33C, 0.5C, 1C, 1.5C, 2C, etc.).
[0015] Preferably, the voltage of each independent battery cell is obtained by collecting the voltage between the surface electrode and the negative electrode tab.
[0016] Preferably, the mixed cathode material is divided into two parts, namely, lithium iron phosphate material and ternary material, or original cathode material and lithium supplement. When the mixed cathode material is divided into lithium iron phosphate material and ternary material, the test method of the present invention can be used to determine the charging strategy of the preset rate; when the mixed cathode material is divided into original cathode material and lithium supplement, the test method of the present invention can be used to determine the optimal formation step of decomposition of the lithium supplement.
[0017] Preferably, the lithium supplement is lithium ferrite or lithium nickelate, and the lithium supplement accounts for ≤5% of the mass percentage of the mixed cathode material.
[0018] The present invention also provides an application of any of the above test methods for measuring current distribution in a mixed cathode lithium battery, which is used to determine the optimal charging strategy for a preset rate when a mixed cathode is formed by lithium iron phosphate material and ternary material; or to determine the optimal formation step for decomposing a lithium supplement agent when a lithium supplement agent is added to the original cathode material.
[0019] Ternary materials have the characteristics of high capacity and high operating voltage platform, good low temperature performance and good rate performance. Iron-lithium materials have the characteristics of good safety performance and long cycle performance. In order to ensure the low temperature performance, energy density and safety advantages of power batteries, a cathode mixed with iron-lithium positive electrode and ternary materials is also an important development direction for power batteries. Since the current contributed by iron-lithium and ternary materials at preset rates and different voltage segments is constantly changing, different currents are required for charging and discharging in different voltage segments to ensure that iron-lithium and ternary materials basically maintain the preset rate charging throughout the charging and discharging section.
[0020] In order to fully decompose the lithium supplement, a relatively small charging rate is generally required, usually 0.05C or lower. However, the formation current of lithium iron can reach 0.2C. Therefore, the charging and discharging strategy should be adjusted for different voltage ranges to maximize the decomposition capacity.
[0021] Preferably, determining the optimal charging strategy under a preset rate specifically includes:
[0022] Under the condition of charging at a preset rate, the current obtained by each material in the mixed cathode within the charging voltage range is measured, the current mutation point of each material in the mixed cathode is determined, and the entire charging voltage range is divided into multiple sections using the charging voltage corresponding to the mutation point;
[0023] Adjust the charging current of each voltage segment, measure the current allocated to each material in the mixed cathode and calculate the actual charging rate of each material. The charging current that ensures the actual charging rate of all materials is as close to or equal to the preset rate as possible is taken as the optimal current. The optimal charging strategy can be obtained based on each voltage segment and the corresponding optimal current.
[0024] Further, the actual charge rate of each material is calculated by: according to the mass m of the lithium battery mixed cathode and the mass specific capacity B of each material and the mass percentage a in the mixed cathode, the standard current of each material at 1C rate is calculated = m*a*B / 1h (mass of the mixed cathode*mass percentage*mass specific capacity of each material / 1 hour), then the actual charge rate of each material = divided current / standard current. The unit of B is mAh / g.
[0025] Preferably, determining the optimal formation process steps for decomposing the lithium supplement agent specifically includes:
[0026] The battery is formed according to each preset formation step, the current obtained by the lithium supplement agent is measured and the current obtained by the lithium supplement agent is integrated according to time to obtain the decomposition capacity of the lithium supplement agent;
[0027] Among the preset formation steps, the one with the highest decomposition capacity of the lithium supplement is selected as the optimal formation step.
[0028] The beneficial effects of the present invention include:
[0029] 1. The present invention adopts the hybrid system equivalent design concept to disassemble the hybrid system battery into multiple independent cells. The independent cell system is designed to refer to the original battery as much as possible. The surface electrodes are used inside the independent cells to make the entire cell equivalent to a pure ohmic resistor. All independent cells are connected in parallel to be equivalent to the original hybrid system. The real-time reaction current of different materials in the original hybrid system is obtained by testing the surface electrodes and negative electrode voltage of each independent cell, and more reasonable working conditions are designed for the battery charging and discharging performance evaluation of the hybrid system to ensure the rate performance and long cycle performance of the hybrid system. The hybrid system equivalent concept of the present invention can also be applied to other batteries such as sodium batteries.
[0030] 2. When the hybrid system is a mixture of ternary and iron-lithium materials, it is disassembled into ternary independent cells and iron-lithium independent cells according to the surface load. After connecting in parallel and testing the independent cells, the current contributed by the electrochemical reaction of ternary and iron-lithium under different working conditions can be obtained. Different currents are used for charging and discharging in different voltage sections to ensure that the iron-lithium and ternary materials are basically charged at the preset rate during the entire charging and discharging section, thereby avoiding damage to the material structure caused by high-rate charging and affecting the cycle performance of the entire hybrid system.
[0031] 3. When the mixed system is obtained by mixing the original cathode material + lithium supplement, it is disassembled into the original cathode material independent battery cell and the lithium supplement independent battery cell according to the surface loading. After being connected in parallel, the current contributed by the electrochemical reaction of the original cathode material and the lithium supplement under different working conditions can be obtained according to the independent battery cell test. Among the many formation steps to be screened, the decomposition capacity of the lithium supplement can be obtained by integrating the contribution current of the lithium supplement independent battery cell with time. By selecting the formation step with the highest decomposition capacity, the optimal formation step for fully decomposing the lithium supplement can be quickly obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0034] Figure 1 Schematic diagram of the morphology of the porous surface electrode;
[0035] Figure 2 Schematic diagram of constructing a pure electronic circuit for the surface electrode and the negative electrode tab in an independent battery cell;
[0036] Figure 3 A schematic diagram of a hybrid cathode system disassembled into two independent cells in parallel;
[0037] Figure 4 It is a schematic diagram of parallel connection of independent lithium iron battery cells and independent ternary battery cells;
[0038] Figure 5 It is a schematic diagram of the parallel connection of the original cathode material independent battery cell and the lithium supplement independent battery cell;
[0039] Figure 6 is the current-voltage straight line of the iron-lithium independent battery cell in Example 1;
[0040] Figure 7 is the current-voltage straight line of the ternary independent battery cell in Example 1;
[0041] Figure 8 is the current-voltage straight line of the independent battery cell of the original cathode material in Example 3;
[0042] Fig. 9 It is the current-voltage straight line of the independent battery cell containing lithium supplement in Example 3. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0045] In addition to the development of conventional iron-lithium materials and ternary materials, battery system development also involves the design and development of hybrid cathodes. The charging and discharging strategies for hybrid systems usually need to consider the materials that actually participate in the reaction within different voltage ranges. Therefore, it is necessary to accurately measure the reaction current of each material in the hybrid system.
[0046] Lithium replenishers are also called "pre-lithiation" or "pre-lithium insertion". They are used to add lithium to the inside of the lithium battery before it works to replenish lithium ions, so as to offset the irreversible lithium loss and thus increase the total capacity and energy of the battery. The mixed system formed between the existing lithium replenishers and the original cathode materials (the original cathode materials can be one or more combinations of lithium iron phosphate, ternary materials, lithium iron manganese, lithium cobalt oxide, and lithium-rich manganese-based materials) will also involve current distribution. However, due to the different voltage ranges corresponding to different positive electrode materials, the current distributed by the lithium replenisher is difficult to measure. Generally, charging and decomposition are performed according to empirical steps, and it is impossible to select the formation step with the maximum decomposition capacity according to actual conditions. Therefore, it is necessary to accurately measure the reaction current of the lithium replenisher and the original cathode material in the mixed system to ensure that the lithium replenisher is fully decomposed.
[0047] In view of the inability to measure the current distribution of multiple materials in the current hybrid system, the present invention adopts the hybrid system equivalent design idea to divide the hybrid system battery into multiple separate cells, and then designs a parallel structure. By using the surface electrode inside a single cell, the entire cell is equivalent to a pure ohmic resistor, and the real-time reaction current of different materials can be tested based on the surface electrode and the negative electrode voltage side, so as to design a more reasonable working condition for the hybrid system cell charging and discharging performance evaluation, and ensure the rate performance and long cycle performance of the hybrid system.
[0048] The present invention intends to provide a test method for measuring current distribution in a mixed cathode lithium battery, comprising the following steps:
[0049] (1) preparing independent cells according to the surface loading of each material in the lithium battery mixed cathode, and each independent cell is provided with a surface electrode on the negative electrode to form a pure electronic circuit with the negative electrode tab;
[0050] (2) Determine the equivalent resistance of each independent battery cell;
[0051] (3) After all independent battery cells are connected in parallel, the voltage of each independent battery cell is collected under preset power-on conditions, and the current passing through each independent battery cell is calculated based on the equivalent resistance, which is the current corresponding to each material in the mixed cathode under the preset power-on conditions.
[0052] In the above step (1), the surface loading of each material is calculated as follows: the overall surface loading of the mixed cathode is A, the mass percentage of each material in the mixed cathode is a, and the surface loading of each material = A·a. When preparing independent battery cells, except for the cathode which is a pure material, the remaining electrolytes, separators, negative electrodes, etc. are as consistent as possible with the original mixed system to avoid introducing new variables. The surface electrode material of each independent battery cell is consistent with the negative electrode current collector material of each independent battery cell. The consistency of the two materials facilitates the smooth transmission of the loop current. Generally, the negative electrode of a lithium battery uses copper foil as the current collector. Therefore, a porous copper foil or copper mesh can be used as the surface electrode on the negative electrode surface (such as Figure 1Each surface electrode is in the shape of a long strip and extends out of the packaging material of the independent battery cell, so as to be connected with the negative electrode tab to form a loop.
[0053] The key to the present invention is to prepare each material into an independent battery cell, which is equivalent to a resistor, a resistor that does not change with the charging SOC and charging current. Common resistors used in lithium batteries include DC internal resistance and AC internal resistance, both of which change with SOC and test conditions, and therefore cannot be well equivalent to resistance. In the present invention, the independent battery cell adopts a porous surface electrode structure on the negative electrode surface, which can construct a pure electronic circuit between the surface electrode and the negative electrode tab, and has the properties of ohmic resistance. Therefore, under different currents, the voltage between the surface electrode and the negative electrode side of the independent battery cell satisfies the linear Ohm's law. The independent battery cell of the present invention can be provided with a voltmeter between the surface electrode and the negative electrode tab, which is used for subsequent voltage measurement of the independent battery cell under various working conditions (such as Figure 2 As shown, the orange color above is the surface electrode, and a voltmeter is set between the surface electrode and the negative electrode ear).
[0054] In the above step (2), the equivalent resistance of each independent battery cell is determined by the following method: the voltage of each independent battery cell is collected under multiple current conditions (at least 5 points are taken at intervals), and the collected voltage and current are fitted with a straight line, and the equivalent resistance value is obtained according to the slope of the straight line. On the current-voltage straight line with the current as the horizontal axis and the voltage as the vertical axis, the slope of the straight line is the equivalent resistance value.
[0055] When the hybrid system consists of two materials A and B, the independent cells prepared by material A are connected in parallel. Figure 3 As shown, the voltage of each independent battery cell is collected under the preset power-on condition, and the current passing through each independent battery cell is calculated based on the equivalent resistance, that is, the current corresponding to materials A and B under the preset power-on condition.
[0056] Through the hybrid system equivalent design, the hybrid system battery is divided into two separate cells, and then the parallel structure is designed. By using the surface electrode inside a single cell, the entire cell is equivalent to a pure ohmic resistor. The real-time reaction current of different materials can be tested based on the surface electrode and the negative electrode voltage side, and a more reasonable charging strategy can be designed for the hybrid system cell charging and discharging performance evaluation to ensure the rate performance and long cycle performance of the hybrid system.
[0057] Based on a general inventive concept, the embodiments of the present application also provide a specific application of one or more test methods for measuring current distribution in a hybrid cathode lithium battery, which is used to determine the optimal charging strategy for a preset rate when a mixed cathode is formed by multiple materials; or to evaluate the optimal formation step for decomposing a lithium supplement when a lithium supplement is added to the cathode iron-lithium material.
[0058] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0059] Example 1
[0060] This embodiment provides a test method for measuring current distribution in a mixed cathode of ternary and iron-lithium materials, and the steps are as follows:
[0061] (1) Determine the surface loading of ternary and iron-lithium materials in the hybrid cathode of lithium batteries. The double-sided loading of the hybrid cathode system is A = 400 g / cm 2 It is known that the mass proportions of iron-lithium and ternary materials are 80% and 20% respectively. According to the calculation of surface loading = A·a, the double-sided loading of iron-lithium material is 320g / cm 2 , the double-sided loading of ternary materials is 80g / cm 2 ; Prepare soft-pack independent battery cells according to their respective surface loadings of iron lithium and ternary materials. The graphite negative electrode of each independent battery cell is provided with a surface electrode material of porous copper foil. The surface electrode is in the shape of a long strip and extends out of the packaging material of the soft-pack independent battery cell. A voltmeter is connected between the surface electrode and the negative electrode tab of each independent battery cell.
[0062] (2) The two independent cells were charged with currents of 10, 30, 60, 90, 120 and 150 mA respectively, and the corresponding voltages were collected. The specific values are shown in Table 1.
[0063] Table 1 Independent cell current and corresponding acquisition voltage
[0064]
[0065]
[0066] like Figure 6-7 As shown, the current-voltage straight line obtained by fitting the independent iron-lithium battery cell is y=0.0106x+0.0015, and the iron-lithium equivalent resistance is 10.6mΩ according to the slope; the current-voltage straight line obtained by fitting the ternary independent battery cell is y=0.0043x+0.0002, and the ternary equivalent resistance is 4.3mΩ according to the slope.
[0067] (3) Figure 4 As shown, the iron-lithium independent battery cell and the ternary independent battery cell are connected in parallel (the positive electrode of the iron-lithium independent battery cell is connected to the positive electrode of the ternary independent battery cell to lead out the total positive electrode, and the negative electrode of the iron-lithium independent battery cell is connected to the negative electrode of the ternary independent battery cell to lead out the total negative electrode, so that the two can be connected in parallel).
[0068] For example, when the preset power-on condition is 60mA charging, the parallel system is charged with a current of 60mA, and the values of the voltmeters of each independent battery cell at 3.1V, 3.3V and 4V are recorded respectively, as shown in Table 2. Then the current values of the iron-lithium independent battery cell and the ternary independent battery cell are calculated according to the values / equivalent resistance of the battery cell voltmeter, that is, the current contributed by the electrochemical reactions of the iron-lithium material and the ternary material of the mixed cathode system under the same 60mA charging condition.
[0069] Table 2 Voltage and current of each independent battery cell
[0070] 60mA current charging voltage (V) 3.1V 3.3V 4V Lithium iron V negative (mV) 0.5512 0.48972 0.0212 Three-element V meter negative (mV) 0.0344 0.05934 0.2494 Lithium iron current (mA) 52 46.2 2 Ternary current (mA) 8 13.8 58 Lithium iron current percentage 86.7% 77.5% 3.3% Ternary current percentage 13.3% 22.5% 96.7%
[0071] Through this battery design, the current contributed by the electrochemical reaction of the two cathode materials in different hybrid systems under different working conditions can be determined. The current of each independent battery cell in parallel / the sum of the currents of all independent batteries * 100% is the percentage of current corresponding to the material in the hybrid cathode under the same working conditions.
[0072] Example 2
[0073] This embodiment applies the test method of current distribution in the mixed cathode of ternary and iron-lithium materials in embodiment 1 to determine the optimal charging strategy for the preset rate, as follows:
[0074] For a system where the mass ratio of iron-lithium and ternary materials is 80:20, assuming that the mass of the mixed cathode in the battery is m = 0.8g. The mass specific capacity of iron-lithium is B = 146mAh / g, a = 80%; the mass specific capacity of ternary materials is B = 170mAh / g, a = 20%, then the total capacity of the battery is 120mAh, and the specific calculation process is as follows:
[0075] 0.8g*170mAh / g*20%+0.8g*146mAh / g*80%=120mAh,
[0076] Iron lithium 1C rate standard current = 0.8g*146mAh / g*80% / 1h = 93mA,
[0077] Ternary 1C rate standard current = 0.8g*170mAh / g*20% / 1h = 27mA.
[0078] If the battery cell is to be charged and discharged at a preset rate of 2C, the charging current is 240mA, and the parallel system is charged at a charging current of 240mA, the current obtained by each independent battery cell within the charging voltage range (2-4.25V) is measured, that is, the current obtained by each material in the mixed cathode with the voltage, and the current mutation point of each material in the mixed cathode is determined. The charging voltage corresponding to the mutation point (3.1V and 3.55V in this embodiment) is used to divide the entire charging voltage range into 2.0V≤charging voltage≤3.1V, 3.1V<charging voltage≤3.55V, and 3.55V<charging voltage≤4.25V;
[0079] Adjust the charging current of each voltage segment, measure the current of each material in the mixed cathode and calculate the real charging rate of each material, and take the charging current when the real charging rate of all materials is as close to or equal to the preset rate as possible as the optimal current, and the optimal charging strategy can be obtained according to each voltage segment and the corresponding optimal current. The optimal 2C charging strategy determined in this embodiment is shown in Table 3.
[0080] Table 3 Equivalent 2C charging strategy for a system with a mixing mass ratio of 80:20 between lithium iron and ternary materials
[0081]
[0082]
[0083] Example 3
[0084] This embodiment provides a test method for measuring the current distribution in the original cathode material and the lithium supplement agent after lithium supplementation, which is as follows:
[0085] (1) The original cathode material (all iron-lithium material) is 84g, the mass of the lithium supplement lithium ferrite material is 2.6g, and the mass proportions of the iron-lithium material and the lithium supplement lithium ferrite are 97% and 3% respectively. The total surface loading after lithium supplementation is (double-sided loading) A = 400g / m 2 The surface loading of lithium iron material is 388g / m 2 , the surface loading of lithium supplement is 12g / m 2 , the iron-lithium material and the lithium supplement are prepared into soft-pack independent cells according to their respective surface loadings. The graphite negative electrode of each independent cell is provided with a surface electrode material of porous copper foil. The surface electrode is in the shape of a long strip and extends out of the packaging material of the soft-pack independent cell. A voltmeter is connected between the surface electrode and the negative electrode tab of each independent cell.
[0086] (2) Two independent battery cells, the capacity of the iron-lithium battery cell is 11600mAh, and the capacity of the lithium-supplemented battery cell is 1300mAh. They are charged with the currents shown in the following table and the corresponding voltages are collected. The specific values are shown in Table 4.
[0087] Table 4 Independent cell current and corresponding acquisition voltage
[0088] Lithium iron test current (mA) Iron lithium V negative (mV) Lithium replenishment test current (mA) Lithium supplement V meter negative (mV) 2400 27.35 130 0.442 4000 44.98 260 0.893 6000 67.76 325 1.135 12000 135.6 390 1.361 18000 202.1 650 2.278 Equivalent resistance (mΩ) 11.2 Equivalent resistance (mΩ) 3.5
[0089] like Figure 8-9 As shown, the current-voltage straight line obtained by fitting the independent iron-lithium battery cell is y=0.0112x+0.3814, and the equivalent resistance of the iron-lithium is 11.2mΩ; the current-voltage straight line obtained by fitting the independent lithium supplement battery cell is y=0.0035x-0.019, and the equivalent resistance of the lithium supplement is 3.5mΩ.
[0090] (3) Figure 5 As shown, the iron-lithium independent battery cell and the lithium supplement independent battery cell are connected in parallel (the positive electrode of the iron-lithium independent battery cell is connected with the positive electrode of the lithium supplement independent battery cell to lead out the total positive electrode, and the negative electrode of the iron-lithium independent battery cell is connected with the negative electrode of the lithium supplement independent battery cell to lead out the total negative electrode, so that the two can be connected in parallel). Figure 6 As shown. Under the preset charging conditions (i.e., 2500mA charging to 3.65V, 625mA charging to 4.25V, constant voltage charging to a current less than 62.5mA), the voltage of each independent battery cell is collected, and the current passing through each independent battery cell is calculated based on the equivalent resistance, which is the current corresponding to the iron-lithium material and the lithium supplement in the mixed cathode under the same power-on conditions, as shown in Table 5 below (because the voltage is accurate to two decimal places, the following 3.51-3.65V represents the case of 3.50V<charging voltage≤3.65V, 3.66-4.0V represents the case of 3.65V<charging voltage≤4.0V, and 4.01-4.25V represents the case of 4.0V<charging voltage≤4.25V).
[0091] Table 5 Voltage and current of each independent battery cell
[0092] Charging voltage 2.5-3.5V 3.51-3.65V 3.66-4.0V 4.01-4.25V Iron lithium V negative (mV) 28.22 27.320 0.843 0 Lithium supplement V meter negative (mV) 0 0.280 1.911 2.255 Lithium iron current (mA) 2520 2440 75 0 Lithium replenishment current (mA) 0 80 550 625 Lithium iron current percentage 100% 96.8% 12% 0 Lithium replenishment current percentage 0 3.2% 88% 100%
[0093] Example 4
[0094] In this embodiment, the test method of the current distribution of the original cathode material and the lithium supplement agent in embodiment 3 is applied to determine the optimal formation step for decomposition of the lithium supplement agent, as follows:
[0095] A plurality of formation steps are preset, and the independent battery cell systems connected in parallel are formed according to each formation step. The current distributed to the lithium supplement battery cell is measured and the distributed current is integrated according to time to obtain the actual decomposition capacity of the lithium supplement. The capacity that lithium ferrite can contribute is 650 mAh / g. When the actual decomposition capacity per gram of lithium ferrite is greater than 585 mAh / g (i.e., it has reached 90%), the formation condition is good.
[0096] Formation step 1: Charge at 2500mA to 3.65V, charge at 625mA to 4.25V, and charge at constant voltage until the current is less than 62.5mA.
[0097] Formation step 2: Charge at 2500mA to 3.65V, charge at 310mA to 4.25V, and charge at constant voltage until the current is less than 31mA.
[0098] Formation step 3: Charge at 2500mA to 3.65V, charge at 160mA to 4.25V, and charge at constant voltage until the current is less than 16mA.
[0099] The results of the current integration over time for the three formation steps are shown in Table 6 below.
[0100] Table 6 Capacity and gram capacity contributed by lithium ferrite in different formation steps
[0101] Forming process Lithium iron oxide capacity (mAh) Actual decomposition capacity per gram (mAh / g) Chemical process 1 943.8 363 Forming step 2 1183 455 Forming step 3 1606.8 618
[0102] From Table 6, it can be seen that the actual decomposition capacity of lithium ferrite per gram in formation step 3 is the largest, up to 618 mAh / g, which can contribute about 95% of the total capacity, that is, formation step 3 is the optimal formation step.
Claims
1. A test method for measuring current distribution in a mixed cathode lithium battery, characterized in that: include: Prepare independent cells according to the surface loading of each material in the lithium battery mixed cathode, and each independent cell is provided with a surface electrode on the negative electrode to form a pure electronic circuit with the negative electrode tab; Determine the equivalent resistance of each independent battery cell; After all independent battery cells are connected in parallel, the voltage of each independent battery cell is collected under preset power-on conditions, and the current passing through each independent battery cell is calculated based on the equivalent resistance, which is the current corresponding to each material in the mixed cathode under the preset power-on conditions.
2. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 1, characterized in that: The surface loading of each material is calculated as follows: the overall surface loading of the mixed cathode is A, the mass percentage of each material in the mixed cathode is a, and the surface loading of each material = A·a.
3. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 1, characterized in that: The independent battery cells are hard-shell battery cells or soft-pack battery cells. The surface electrode material of each independent battery cell is consistent with the negative electrode current collector material. Each surface electrode is in the shape of a long strip and extends out of the packaging material of the independent battery cell.
4. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 1, characterized in that: Determining the equivalent resistance of each independent battery cell specifically includes: collecting the voltage of each independent battery cell under multiple current conditions, performing a straight line fitting between the collected voltage and current, and obtaining the equivalent resistance value according to the slope of the straight line.
5. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 1 or 4, characterized in that: The voltage of each independent battery cell is obtained by collecting the voltage between the surface electrode and the negative electrode tab.
6. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 1, characterized in that: The mixed cathode material is divided into two parts, namely, lithium iron phosphate material and ternary material; or original cathode material and lithium supplement.
7. The test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 6, characterized in that: The lithium supplement is lithium ferrite or lithium nickelate, and the lithium supplement accounts for ≤5% of the mass percentage of the mixed cathode material.
8. An application of the test method for measuring current distribution in a mixed cathode lithium battery as claimed in any one of claims 1 to 7, characterized in that: It is used to determine the optimal charging strategy for a preset rate when a mixed cathode is formed by lithium iron phosphate material and ternary material; or it is used to evaluate the optimal formation step for decomposing the lithium supplement agent when a lithium supplement agent is added to the original cathode material.
9. Application of the test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 8, characterized in that: Determine the optimal charging strategy under the preset rate, including: Under the condition of charging at a preset rate, the current obtained by each material in the mixed cathode within the charging voltage range is measured, the current mutation point of each material in the mixed cathode is determined, and the entire charging voltage range is divided into multiple sections using the charging voltage corresponding to the mutation point; Adjust the charging current of each voltage segment, measure the current allocated to each material in the mixed cathode and calculate the actual charging rate of each material. The charging current that ensures the actual charging rate of all materials is as close to or equal to the preset rate as possible is taken as the optimal current. The optimal charging strategy can be obtained based on each voltage segment and the corresponding optimal current.
10. Application of the test method for measuring current distribution in a mixed cathode lithium battery as claimed in claim 8, characterized in that: Evaluate the optimal formation steps for lithium supplement decomposition, including: The battery is formed according to each preset formation step, the current obtained by the lithium supplement agent is measured and the current obtained by the lithium supplement agent is integrated according to time to obtain the decomposition capacity of the lithium supplement agent; Among the preset formation steps, the one with the highest decomposition capacity of the lithium supplement is selected as the optimal formation step.
Citation Information
Patent Citations
Electrode structure provided with resistors
CA3013692A1
Simulation method and device of battery system, electronic equipment and storage medium
CN117590244A
Charge state estimation device of secondary battery
JP2017026443A
Power supply system control device
JP2021165675A